Comparative effectiveness of the tumour diagnostics, CA 19-9, CA 125 and carcinoembryonic antigen in patients with diseases of the digestive system. Issue 3 (March 1987) - Sakamoto, K; Haga, Y; Yoshimura, R; Egami, H; Yokoyama, Y; Akagi, M
Abstract : Serum concentrations of CA 19-9, CA 125 and carcinoembryonic antigen (CEA) in 145 patients with gastrointestinal carcinomas and 89 with non-neoplastic diseases were determined to compare the clinical usefulness of these tumour markers. Significantly fewer positive cases were obtained with serum CA 19-9 (9%) and CA 125 (8%) tests than the CEA test (22%) (both p less than 0.05) in patients with benign diseases, while comparable sensitivities were achieved with the CA 19-9 (44%) test, the CA 125 (41%) test and the CEA test (47%) in those with a carcinoma. High incidences of raised concentrations of serum CA 19-9 and CA 125 were observed in case of cancer of the pancreas (CA 19-9: 87%, CA 125: 67%) and biliary tract (CA 19-9: 63%, CA 125: 48%). Combined tests of CA 19-9 and CA 125 revealed increments in the sensitivity (61%) and provided a higher specificity (87%) than that of the single CEA test (78%). These combined tests were most useful for a differential diagnosis of pancreatic carcinoma (97% positive) and biliary tract carcinoma (74%) from chronic pancreatitis (4%) and cholelithiasis (0%), respectively. Studies on the relations of clinical staging and serum concentrations of CA 19-9 and CA 125 revealed significant rises in cases of disseminated carcinoma. These results clearly show that serum CA 19-9 and CA 125 tests are most pertinent for diagnosing advanced carcinomas of organs in the digestive system.